The Relationship between Public Service Motivation and Work Performance: A study in Finnish public organizations - Jan , Muhammad (My University, 2016)
The purpose of this study was to scrutinize the relationship between public service motivation and work performance by engaging three dimensions which include determination of motivational factors, impact of public service motivation on work performance and identification of motivated employees. Quantitative research method was adopted. A cross-sectional survey was conducted in Finnish public organizations to collect the research data. Descriptive statistics and statistical mean were applied in data analysis to draw the results. The research potentially contributes to the field of public service motivation in relation to employee performance. It presents the construct of public service motivation in relation to work performance with three dimensions. The multidimensionality of the study was transformed into a PSM-Performance research model. It offered a PSM-Performance measurement scale to the research field. The study found a positive relationship between public service motivation and work performance. It further finds that there are several motivating factors which stimulate employee behavior to produce higher performance. Mostly of the public employees were found motivated in the subject Finnish public organizations. It confirms the previous studies on the importance of public service motivation. The public managers may consider the results of the study to focus on strong areas and to cope with weak areas regarding PSM and performance in their organizations. This thesis study points out new research directions in organizational perspective for the public managers and researchers. It suggests to public organizations for recognizing the link between PSM and work performance.
Keywords: Public service motivation; work performance; motivation; motivational factors; motivated employee; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|